Lexical selection and construction of argumentativeness in journalistic texts - Neves, Herbertt (Revista Letras Raras, 2022)
This study aims to examine the argumentative positioning of comments on the 2018 elections, focusing on the use of items from the lexical system. The corpus is of twelve texts analyzed in a qualitative, descriptive and documentary research. It isevenly composed of the text genres opinion pieces and editorial. All texts were published by the three main news papers ofthe city of Recife during the second round of the 2018 elections. The focus is on the way in which nouns, adjectives andverbs linked to the theme of elections acted as contextualization cues (GUMPERZ, 2013) for the construction of the argumentative direction of the journalistic domain as a whole. We draw on a socio-interactional conception of language and lexicon (ANTUNES, 2012; MARCUSCHI, 2003; 2004; CARDOSO, 2015). Within our sample, we find a close relationshipamong the text genre, the definition of the author's position and the choice of lexical items related to the topic under debatein a text.